Relationship of -31G/C (rs9904341) polymorphism in the survivin gene BIRC5 and the risk of bladder cancer - E. E. Bashmakova; N. S. Panamarev; A. N. Kudryavtsev; D. V. Chernyaev; E. V. Slepov; R. A. Zukov; L. A. Frank (Сибирский онкологический журнал)
Purpose: To study the relationship between the -31G/C (rs9904341) polymorphism in the promoter region of the survivin protein gene and the predisposition to bladder cancer (BC) in patients of the Krasnoyarsk region. Material and methods. The allelic composition of the studied gene was determined in a group of 158 BC patients, consisting of 30 women and 128 men (mean age 65.6 ± 10.7, median: 66.5; C25–C75: 59–72). The control group included 117 healthy donors and consisted of 27 women and 90 men with an average age of 60.2 ± 5.1 (median: 60; C25–C75: 57–63.25). The allelic composition was determined using the bioluminescent method. A sample with the GC genotype confirmed by sanger sequencing (center for collective use “genomika”, Novosibirsk, Russia) was used as a control. The Mann–Whitney U test was used to compare quantitative data. the studied sample was in Hardy–Weinberg equilibrium (p>0.5). The pearson χ2 test was used to compare the frequencies of gene variants among BC cases and control samples. The association between variants rs9904341 and BC was assessed in terms of odds ratio (OR) with a 95 % confidence interval (CI); p values<0.05 were considered significant. Results. The allelic composition was determined for the genes of patients and control group participants: GG – 62 (39.2%) vs 43 (36.8%); GC – 82 (51.9%) vs 54 (46.2%); CC – 14 (8.9%) vs 20 (17.15%). The relationship between the presence of the C allele and BC was assessed using the recessive inheritance model, combining all carriers – heterozygotes and homozygotes. The frequency of occurrence of genotypes for patients and the control group was established: GG + GC – 144 (91.1%) vs 97 (82.9%); CC – 14 (8.9%) vs 20 (17.1%). Thus, carriers of the CС genotype were significantly less in patients: OR (95% CI) 0.47 (0.23–0.98), p=0.04. The relationship with tumor invasion was not significant (p=0.08). Conclusion. Based on the results of detecting the rs9904341 (G/C) polymorphism among BC patients of the Krasnoyarsk region, a protective effect of the carriage of the CC genotype was found. In order to study the allelic composition with the threat of recurrence of the disease, additional research is needed.